Extended time on an unspeeded assessment improves neither test anxiety nor performance - Marcus, Nicole; Mueller, Liam O'Connor; Cooke, James E. (Frontiers in Education, 2025)
IntroductionThe amount of time students are given to complete an assessment is a pragmatic element to the assessment itself. Assessments that provide the vast majority (>80%) of students sufficient time for completion are said to be “unspeeded.” However, even if an assessment is unspeeded students may experience test anxiety if the assessment is timed, and test anxiety can cause students to underperform relative to their ability. While providing unlimited time to complete assessments would alleviate anxiety and improve test scores, this is unrealistic in most classroom settings. The current study assessed whether increasing the time students had to complete a timed, unspeeded exam would improve performance by lowering test anxiety.MethodsTest anxiety surveys were administered before and after midterm exams in two sections of an undergraduate classroom: an unspeeded control section which had 1 h to complete the exam, and a treatment section which had 2 h to complete the exam.ResultsDoubling the amount of time students have on an already-unspeeded exam improved neither test performance nor test anxiety. However, students in the treatment condition were significantly less likely to report wanting more time on the exam in a post-assessment survey.